Prototype of a zero-field-cooled YBCO bearing with continuous ring permanent magnets - Arsénio, António (2019)
Based on the levitating design of the Zero-Field-Cooled (ZFC) Maglev previously developed, a novel horizontal ZFC superconductor magnetic bearing (SMB) is currently being developed. However, simulations have shown that its stator and rotor made of YBCO bulks and NdFeB permanent magnets (PM), respectively, present significant magnetic discontinuities. These produce asymmetries on the bearing rotation and several stable and unstable position angles that prevent the SMB from rotating smoothly, leading to a step motor like sort of rotation. Those drawbacks are now avoided by using ring shape PMs, leading not only to a smooth rotation of the SMB but also increasing its stability. New three-dimensional finite element method simulations and a set of experimental tests with the new SMB show in this paper the viability and increased performance when ring shape PMs are used. Finally, experimental results using the prototype also show that the model fits very well with the laboratory test results.